Genotype, Mortality, Morbidity, and Outcomes of 3β-Hydroxysteroid Dehydrogenase Deficiency in Algeria - Ladjouze, Asmahane; Donaldson, Malcolm; Plotton, Ingrid; Djenane, Nacima; Mohammedi, Kahina; Tardy-Guidollet, Véronique; Mallet, Delphine; Boulesnane, Kamélia; Bouzerar, Zair; Morel, Yves; Roucher-Boulez, Florence (Frontiers in Endocrinology, 2022)
Background: 3β-hydroxysteroid dehydrogenase 2 (3βHSD2) deficiency is a rare form of congenital adrenal hyperplasia (CAH), with less than 200 cases reported in the world literature and few data on outcomes. Patients and methods: We report a mixed longitudinal and cross-sectional study from a single Algerian center between 2007 and 2021. Virilisation and under-masculinisation were assessed using Prader staging and external masculinisation score (EMS), pubertal development according to Tanner. Adrenal steroids were measured using mass spectrophotometry (LC-MS/MS). Genetic analysis of HSD3B2 was performed using Sanger sequencing. Results: A 3βHSD2 defect was confirmed in 6 males and 8 females from 10 families (8 consanguineous), with p.Pro222Gln mutation in all but two siblings with a novel deletion: c.453_464del or p.(Thr152_Pro155del). Probable 3βHSD2 deficiency was diagnosed retrospectively in a further 6 siblings who died, and in two patients from two other centers. In the genetically confirmed patients, median (range) age at presentation was 20 (0-390) days, with salt-wasting (n=14) and genital anomaly (n=10). Prader stage for female patients was 2 (1-2) with no posterior fusion of the labia, EMS for males was 6 (3-9). Median (range) [reference range for 1-10 years] values at diagnosis for 17-hydroxyprogesterone (17-OHP), dehydroepiandrosterone sulphate (DHEA-S) and 17-hydroxypregnenolone (17OHPreg) were: 73.7 (0.37-164.3) [0.4-3.3] nmol/L; 501.2(9.4-5441.3) [30-333] nmol/L and 139.7 (10.9-1500) [0.13-13.7] nmol/l. Premature pubarche was observed in four patients (3F:1M). Six patients (5F:1M) entered puberty spontaneously: 11 (5-13) years in 5 girls and 11.5 years in one boy. Four girls had menarche at 14.3 (11-14.5) years, of whom three developed polycystic ovary syndrome (PCOS). Adrenal rest tumours were found in the testes of three boys and ovaries of three girls, with adrenal gland enlargement mimicking adrenal cortical tumour in one girl. Median IQ was 85.1 (43-105) (n=12), being low (< 80) in three patients. Conclusions: The prevalence of 3βHSD2 deficiency in Algeria appears high, with p.Pro222Gln the most frequent mutation. Mortality is also high, with significant morbidity from PCOS and adrenal rest tumours in adolescence, probably reflecting undertreatment. Since 17-OHP is elevated at presentation, 3βHSD2 deficiency could be diagnosed and treated from birth if newborn screening for CAH was introduced.